2011
DOI: 10.4103/0253-7613.83117
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of nebivolol and atenolol on blood pressure, blood sugar, and lipid profile in patients of essential hypertension

Abstract: Background:Nebivolol is a third-generation β-blocker, with highest β1 selectivity and nitric-oxide-derived vasodilatation. It also exhibits antiproliferative and antioxidant property that has beneficial metabolic profile compared to second-generation β blockers like atenolol. This study was planned to study the comparative effects of nebivolol and atenolol on metabolic parameters in patients with essential hypertension.Materials and Methods:A prospective, randomized, parallel, open-label clinical study was car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
12
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 11 publications
(12 reference statements)
9
12
1
Order By: Relevance
“…These results correlate to the study done by Van Bortel 13 with the exception that no significant changes in HDL cholesterol and TGs were observed in the respective study. However, our findings are in contrast with Pesant et al 20 and Badar et al 21 who showed in their studies that there was no change in lipid parameters in patients on treatment with nebivolol. Similarly, a study by Peter et al in patients of type 2 diabetes with mild to moderate hypertension exhibited no significant changes in serum cholesterol or TGs following treatment with nebivolol, but a significant increase in HDL cholesterol was noted.…”
Section: Discussioncontrasting
confidence: 99%
“…These results correlate to the study done by Van Bortel 13 with the exception that no significant changes in HDL cholesterol and TGs were observed in the respective study. However, our findings are in contrast with Pesant et al 20 and Badar et al 21 who showed in their studies that there was no change in lipid parameters in patients on treatment with nebivolol. Similarly, a study by Peter et al in patients of type 2 diabetes with mild to moderate hypertension exhibited no significant changes in serum cholesterol or TGs following treatment with nebivolol, but a significant increase in HDL cholesterol was noted.…”
Section: Discussioncontrasting
confidence: 99%
“…3 Furthermore, in addition to the changes in lipid levels, more patients in the metoprolol group had initiation of statin therapy or their statin dose increased compared with those in the carvedilol group (32% vs. 11%, p=0.04). 27 Similar results have also been observed in 2 small trials comparing the metabolic effects of nebivolol with atenolol 8 and metoprolol. 11 In a secondary analysis of the large, multinational Carvedilol Or Metoprolol European Trial, patients without DM who were randomized to carvedilol were less likely to develop DM compared with those randomized to metoprolol (HR=0.78, p=0.048).…”
Section: Discussionsupporting
confidence: 72%
“…25, 7 In head-to-head trials, patients with DM who were treated with vasodilating (vs. traditional) beta-blockers had small but significant decreases in hemoglobin A1c levels, improved insulin sensitivity, lower cholesterol levels, less weight gain, and less progression to microalbuminuria. 3, 811 However, these findings have not been confirmed in the real-world clinical practice environment.…”
mentioning
confidence: 87%
“…In this study for 6 months, SBP reduced from 160.13±1.62 mm Hg to 118.93±0.87 mm Hg in atenolol arm and from 159.93±1.62 mm Hg to 116.73±0.91 mm Hg in nebivolol. Similar responses were observed with DBP and HR 33. Thus, whether Indian patients are highly responsive to β blockers or there is contribution by placebo effect needs be investigated further.…”
Section: Discussionmentioning
confidence: 55%